A Scoping Review of Treatment Outcome Measures for Vulvar Intraepithelial Neoplasia. Issue 4 (6th October 2022) - Jamieson, Amy; Tse, Samantha S.; Proctor, Lily; Sadownik, Leslie A.
Abstract : Objective: The goal of this study is to identify a list of clinician-reported outcome measures (CROMs) and patient-reported outcome measures (PROMs) through a review of published studies reporting on any therapeutic interventions for vulvar intraepithelial neoplasia (VIN). Materials and Methods: A systematic search of published studies reporting on any therapeutic interventions for VIN was performed on MEDLINE, Embase, Cochrane Database, PsychInfo, and CINAHL from inception to September 20, 2021, based on predetermined study selection criteria. Data were extracted and analyzed by 2 authors independently using Covidence software. Results: Thirty two of 2386 studies identified met study selection criteria. None of the 32 studies provided an explicit definition of VIN treatment "success." The most common CROM was "clinical response to treatment." The most common scale used to measure this outcome was "complete response/partial response/no response"; however, 17 of 23 studies (73.9%) did not define these values. Laboratory CROMs were reported in 12/32 (37.5%) studies. Patient-reported outcome measures were reported in only 10 of 32 studies(31.3%) —the most common PROM was "symptoms." Only 2 of 32 studies measured PROMs related to "quality of life" domains. Adverse events/treatment-related adverse effects were reported in 24 of 32 studies (75%), although 71% of studies provided no details on how these data were collected. Conclusions: There is a large variation in outcome measures, instruments, and scales used for any clinician-reported treatment outcome such as "clinical response." Most studies do not include patient-reported outcome measures assessing quality of life domains. A Core Outcome Set for the treatment of VIN is needed to improve the quality of VIN research.